Irrigation Scheduling for Young Pongamia (Millettia pinnata (L.) Panigrahi) Trees - Daniel Palacios; Sandra Guzmán; Amir Rezazadeh; Liliana Cano; Lorenzo Rossi; Alan Wright (EDIS)
This publication addresses the influence of irrigation scheduling on water use, plant growth, and development for young pongamia trees (Millettia pinnata (L.) Panigrahi). Written by Daniel Palacios, Sandra M. Guzmán, Amir Rezazadeh, Liliana M. Cano, Lorenzo Rossi, and Alan Wright, and published by the UF/IFAS Department of Agricultural and Biological Engineering, November 2023.